Ivabradine modulates the autonomic nervous system by affecting the "little brain" of the heart: A hypothesis. (August 2019) - Baka, Tomas; Simko, Fedor
Abstract: Ivabradine decreases heart rate by selective inhibition of the If current in the sinoatrial node. Ivabradine is declared to have no direct effect on the autonomic nervous system (ANS). However, there are some data suggesting an (at least indirect) effect of ivabradine on the ANS. The pathomechanism behind is unclear. Based on the complex of plexuses and ganglia in the heart, the existence of the intrinsic cardiac nervous system (ICNS), also known as the "little brain" of the heart, has been suggested. The ICNS is supposed to process information on the cardiac milieu and provide the central nervous system with these data. We put forward a hypothesis that part of ivabradine's protective effects might reside in the modulation of the ANS by affecting the ICNS. Setting a new autonomic balance by ivabradine might be of benefit in the treatment of autonomic dysfunction-related pathologies.